Making Learning Module Using Google Spaces for Kindergarten Teachers in Pangandaran Based on LMS (Learning Management System) - Ari Purno Wahyu Wibowo; Eka Angga Laksana; Sukenda Sukenda; Benny Yustim (Brilliance: Research of Artificial Intelligence, 2025)
Learning process Children of kindergarten age tend to get bored easily and must use a different approach, because at an early age children will get tired easily if taught something tire Computers with attractive visual displays, animations, and sounds can make the learning process feel like playing, so that they are more enthusiastic and motivated. to overcome this, it is necessary to create a more innovative multimedia-based teaching system on the material taught must have parameters that are visual, audio and interactive material, so that the material delivered can be easily measured according to learning outcomes, in this study the author tried to use the help of open source applications based on Google Spacess and LMS (Learning Management System) which can be used by kindergarten teachers in the Pangandaran area, by using this Google Spaces assistance, it turns out that teachers can create the same and more interactive teaching material, in the end with the help of digital media, the material can be adjusted to the individual abilities of each child's speed and can be evaluated directly because for example children who have mastered the material can proceed to the next stage, while on the contrary students who are left behind in learning can repeat more relaxedly repeating the learning, then with the help of teachers and the student learning process can be done independently and not limited by time, because the LMS module can be accessed at any time by students. From the results of the training held for 65 kindergarten teachers, 85% agreed that this LMS application was very helpful in teaching and easy to configure and re-develop.